Interpersonal Psychoanalytic Theory for the 21st Century: Evolving Self - Harris, Sue,; Mayes, Janet R.,; Miller, Marilyn,; Singer, David, (Lexington Books, 2023)
Interpersonal psychoanalytic theory states that people can achieve insight into how, through interactions with people, they became who they are, and how they can change patterns of living that limit further satisfaction. People are born with a blueprint for growth and development that includes self-respect, joy, expansion of experiences, creativity, and ever widening and deepening human interactions. With some exceptions, the mental health profession in the United States is dictated by insurance and pharmaceutical companies, focusing primarily on symptom reduction and social conformity. These goals are inadequate. The goal, as elucidated in this book, is maximizing one's human potential. Interpersonal Psychoanalytic Theory for the 21st Century: Evolving Self is written for practitioners in all areas of mental health and pedagogy, whether or not they are psychotherapists or clinicians. It is also intended for anyone interested in understanding themselves and other people. Additionally, in the spirit of Harry Stack Sullivan, developer of the theory, this volume addresses some pressing issues relevant to interpersonal theory and practice in the twenty-first century social/economic/political milieu.